A SYSTEMATIC APPROACH IN MODERN INTERDISCIPLINARY RESEARCH - Nurmamatova Sevara Kamol qizi; Ruzmetova Diana Komilovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
This paper explores the importance of the systemic perspective in contemporary interdisciplinary research. It outlines how systemic thinking facilitates the integration of various scientific disciplines, the examination of complex structures, and the comprehension of multi-tiered interactions within natural, social, and technological frameworks. Furthermore, the article presents instances of systemic methodology employed in current scientific fields and highlights its benefits for fostering innovative and sustainable solutions.